1985
DOI: 10.1007/bf01799655
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic congenital lactic acidosis by oral administration of dichloroacetate

Abstract: Sodium dichloroacetate (DCA) was administered orally at a dose of 50 mg per kg body weight twice or three times per day to a newborn infant with lactic acidosis of unknown cause (patient 1) and to a 15-year-old boy with mitochondrial encephalomyopathy associated with lactic acidosis (patient 2). In patient 1, during treatment with DCA, DCA accumulated in the blood judging from the findings that the urinary excretion of DCA increased cumulatively and the blood lactate level rapidly decreased to the normal range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…These data suggest that the concomitant administration of a full dosage of thiamine and DCA may be required to achieve maximal activity of PDHC in patients with lactic acidaemia. Therefore, a full dosage of DCA (50 mg/kg every 12 h) and thiamine (100± 200 mg/day) should be given initially to achieve maximal activity of PDHC in patients with thiamine-responsive PDHC de®ciency or lactic acidaemia of unknown origin, especially in those with an acidotic crisis [8]. …”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the concomitant administration of a full dosage of thiamine and DCA may be required to achieve maximal activity of PDHC in patients with lactic acidaemia. Therefore, a full dosage of DCA (50 mg/kg every 12 h) and thiamine (100± 200 mg/day) should be given initially to achieve maximal activity of PDHC in patients with thiamine-responsive PDHC de®ciency or lactic acidaemia of unknown origin, especially in those with an acidotic crisis [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Roodhoft et al [18] administered a combination of camitine, riboflavin, nicotinamide, L-va-line, L-isoleucine, and ubiquinone to a 4-month-old infant with a combined complex I and complex IV defect. Thiamine is the coenzyme for pyruvate dehydrogenase [9,10,21]. The lactate concentration was elevated before therapy in blood and CSF, no comments are available on these values after cessation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report about treatment of mitochondrial myopathy, encephalopathy, lactic acidosis and stroke‐like episodes (MELAS) showed that DCA concentrations in serum should be between 100 and 120 µg/mL 2 h after DCA administration 3 . It has also been reported that the DCA dose must be determined by monitoring the concentration of lactic acid and DCA because DCA tends to accumulate in tissue 4 …”
Section: Discussionmentioning
confidence: 99%